Solvent‐Assisted Anisotropic Cleavage of Transition Metal Carbide into 2D Nanoflakes. Issue 11 (6th August 2021) - Hu, Chen-Xia; Tian, Zhen; Xiao, Qi; Zhu, Zhen-Tong; Li, Xiang-Yang; Dun, Guan-Hua; Wu, Hao-Ran; Tang, Yu-Long; Wang, Qiang; Zhang, Hao-Li
Abstract : Mechanical exfoliation of bulk layered materials into atomic‐layer thin nanosheets has become a general strategy to obtain 2D nanomaterials, which seems intuitively unsuitable for non‐van der Waals crystals. However, a new method is proposed, namely, solvent‐assisted anisotropic cleavage (SAAC), for producing thin nanostructures from transition metal carbides (TMCs), including titanium carbide (TiC) and tungsten carbide (WC). The SAAC method harnesses the intrinsic anisotropic hardness properties of the TMC and enables efficient cleavage of bulk TMC into 2D layers. Under ultrasonication in appropriated solvent, TiC crystals show preferable cleavage along [110] direction and produce 2D nanoflakes. The obtained 2D nanoflakes are successfully applied for ultrafast photonics as saturable absorbers (SAs) in mode‐locked thulium fiber lasers, where stable third‐order harmonically mode‐locked dissipative solitons are realized at 2 μm. The success of the SAAC process opens a new pace toward preparation of 2D nanomaterials. Abstract : Solvent‐assisted anisotropic cleavage method is first used herein to exfoliate non‐van der Waals transition metal carbides into 2D nanosheets successfully, which extends the members of the family of 2D material. These new fabricated TiC and WC 2D nanosheets with unique nonlinear optical properties make them extremely attractive to optical applications.